Variation in thermally induced taste response across thermal tasters - Skinner, Martha; Eldeghaidy, Sally; Ford, Rebecca; Giesbrecht, Timo; Thomas, Anna; Francis, Susan T.; Hort, Joanne (Elsevier, 2018)
Thermal tasters (TTs) perceive thermally induced taste (thermal taste) sensations when the tongue is stimulated with temperature in the absence of gustatory stimuli, while thermal non tasters (TnTs) only perceive temperature. This is the first study to explore detailed differences in thermal taste responses across TTs. Using thermal taster status phenotyping, 37 TTs were recruited, and the temporal characteristics of thermal taste responses collected during repeat exposure to temperature stimulation. Phenotyping found sweet most frequently reported during warming stimulation, and bitter and sour when cooling, but a range of other sensations were stated. The taste quality, intensity, and number of tastes reported greatly varied. Furthermore, the temperature range when thermal taste was perceived differed across TTs and taste qualities, with some TTs perceiving a taste for a small temperature range, and others the whole trial. The onset of thermal sweet taste ranged between 22 and 38°C during temperature increase. This supports the hypothesis that TRPM5 may be involved in thermal sweet taste perception as TRPM5 is temperature activated between 15-35°C, and involved in sweet taste transduction. These findings also raised questions concerning the phenotyping protocol and classification currently used, thus indicating the need to review practices for future testing. This study has highlighted the hitherto unknown variation that exists in thermal taste response across TTs, provides some insights into possible mechanisms, and importantly emphasises the need for more research into this sensory phenomenon.